KONSEP MAHABBAH JALALUDDIN RUMI - assya octafany (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2020)
This article explores Rumi's mahabbah concept. Currently, in society, the concept of love is degrading in meaning, resulting in its constriction. This is because the concept of mahabbah, which we usually refer to as "love," is unfamiliar to the general population. In general, society equates love with liking the other sex. Spite of the fact ,  Rumi asserts that love is not confined to that. The notion of love will be addressed in this study via the lens of Jalaluddin Rumi, specifically the nature of love and its application in life. The findings of this study provide an outline of the type of love that people should possess: love powerful enough to cause someone to love their god.